2021
DOI: 10.3389/fsufs.2020.582834
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Scale and Scope: Exploring Economic Drivers of U.S. Specialty Crop Production With an Application to Edamame

Abstract: Specialty crops are considered high-risk, high-reward, yet growers face differing, and relatively larger risk exposure when compared to traditional row crops. With traditional row crops, economies of scale and scope are key factors to increasing economic profitability. However, increasing economic profit for specialty crop operations present challenges which limit grower ability to easily take advantage of scale and scope economies. The authors discuss production, finance, regulatory, price, and human resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
(6 reference statements)
2
14
0
Order By: Relevance
“…Although our survey respondents somewhat agreed that domestic edamame is available at the grocery store where they most frequently purchase vegetables (mean = 3.6 ± 1.5), they somewhat disagreed that there is a wide range of domestically produced edamame available in the places where they do their grocery shopping (mean = 2.7 ± 1.2; Likert scale: 2 = "Disagree"). This perception is in accordance with the fact the U.S. market is mostly supplied by imports and the domestic production is still low (Neill and Morgan, 2021). Although a negative impression of frozen edamame was not confirmed, our survey respondents agreed that edamame beans sold encased in their pods are better than shelled edamame beans (mean = 4.0 ± 1.4).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Although our survey respondents somewhat agreed that domestic edamame is available at the grocery store where they most frequently purchase vegetables (mean = 3.6 ± 1.5), they somewhat disagreed that there is a wide range of domestically produced edamame available in the places where they do their grocery shopping (mean = 2.7 ± 1.2; Likert scale: 2 = "Disagree"). This perception is in accordance with the fact the U.S. market is mostly supplied by imports and the domestic production is still low (Neill and Morgan, 2021). Although a negative impression of frozen edamame was not confirmed, our survey respondents agreed that edamame beans sold encased in their pods are better than shelled edamame beans (mean = 4.0 ± 1.4).…”
Section: Resultssupporting
confidence: 82%
“…A very similar consumption behavior was reported by the participants of our sensory studies performed over 2 consecutive years in Blacksburg, VA (Carneiro et al, 2021); considering the average of both years, our sensory participants, who were mostly female (55%), reported their intentional vegetable consumption was at least once a day (69%) and consumption of edamame was a few times per year (49%). Even though the demand for edamame in the U.S. has been increasing 12-15% annually (Neill and Morgan, 2021), our studies confirmed the frequency in which consumers include edamame in their diets is still low and it suggests the edamame market has potential to continue growing in the country.…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…Edamame has been a staple in East Asian diets for centuries (Shurtleff & Aoyagi, 2009) and is most frequently consumed as a snack food, appetizer, salad component, or culinary ingredient by many Americans as they continue to demand its versatility and impressive nutritional quality. While the economic potential of edamame has been discovered by many in the United States (Associated Press, 2013;Bennett, 2016;Bernick, 2009;Garber & Neill, 2019;Neill & Morgan et al, 2020;Nosowitz, 2016;Sciarappa et al, 2016), domestic production has largely lagged behind consumer demand causing the majority of edamame consumed in the United States to be imported from overseas.…”
Section: Introductionmentioning
confidence: 99%